Gac / nio composite catalyst and preparation method and application thereof

CN122937796APending Publication Date: 2026-10-20GUANGXI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147652.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,上述超声辅助高级氧化体系在实际应用中仍存在以下不足:(1)该体系采用作为均相催化剂活化过硫酸钠产生自由基,均相催化剂难以从反应体系中分离回收,导致试剂消耗量大、运行成本偏高;(2)在反应过程中易被氧化为,且转化效率较低,导致催化剂活性下降和氧化剂浪费

Benefits of technology

[0021]本发明催化剂用来剥离后的正极材料中GAC在火法回收工艺中可作为碳源,作为还原剂将镍钴锰等金属氧化物还原,降低废旧电池回收过程的能耗和成本,实现高效、快速剥离,保证回收铝箔的完整性;进一步地,本发明剥离方法正极材料大部分以片状形态从铝箔上剥离,GAC/NiO为细小颗粒,将完整的铝箔分拣回收后,剩下的正极材料和GAC/NiO混合物可利用大小尺度差异过筛分离,重复回收GAC/NiO,实现重复利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a GAC / NiO composite catalyst, in which the active phase NiO is supported on the surface of activated carbon, obtained by impregnating activated carbon in an aqueous nickel nitrate solution and calcining it at high temperature. The preparation method and application of this composite catalyst are also disclosed. In the pyrometallurgical recycling process, the GAC in the stripped cathode material can serve as a carbon source and a reducing agent to reduce metal oxides such as nickel, cobalt, and manganese, reducing energy consumption and cost in the waste battery recycling process, achieving efficient and rapid stripping, and ensuring the integrity of the recycled aluminum foil. Furthermore, in the stripping method of this invention, most of the cathode material is stripped from the aluminum foil in sheet form, while GAC / NiO is in fine particles. After the intact aluminum foil is sorted and recycled, the remaining cathode material and GAC / NiO mixture can be separated by sieving based on size differences, allowing for repeated recovery of GAC / NiO and achieving reuse.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, its preparation method, and its application, specifically to a GAC / NiO composite catalyst, its preparation method, and its application. Background Technology

[0002] Waste lithium batteries contain a large amount of valuable metals (lithium, cobalt, nickel, manganese, etc.) and recyclable fluids (aluminum foil), making them of significant resource recovery value. The positive electrode sheet mainly consists of aluminum foil, a binder (usually polyvinylidene fluoride, PVDF), and positive electrode active materials (such as lithium cobalt oxide, lithium iron phosphate, ternary materials, etc.). The PVDF binder between the positive electrode active material and the aluminum foil has strong adhesion, and efficient separation of the two is a crucial step in the pre-treatment process for waste lithium battery recycling.

[0003] In existing technologies, the methods for separating cathode materials from aluminum foil are mainly divided into two categories: physical methods and chemical methods. Physical methods include mechanical crushing separation, organic solvent separation, centrifugal separation, electrostatic separation, and aqueous phase separation; chemical methods include heat treatment, electrolysis, acid and alkali treatment, advanced oxidation, and deep eutectic solvent methods.

[0004] For ultrasound-assisted advanced oxidation processes, existing technologies include ultrasound-assisted... The system employs advanced oxidation technology to selectively degrade the PVDF binder to strip the cathode material. This method utilizes ferrous sulfate. Activating sodium persulfate generates free radicals, which then attack the PVDF molecular chains, achieving effective separation of the positive electrode coating from the aluminum foil in a relatively short time. The specific process involves placing the waste lithium battery positive electrode in a container with a certain amount of dilute sulfuric acid. Then, a certain amount of ferrous sulfate and sodium persulfate solid are weighed and added to the container. The container is then placed in an ultrasonic device for approximately 20 minutes. After the reaction is complete, the aluminum foil and the positive electrode material can be peeled off. However, the above ultrasonic-assisted... The advanced oxidation system still has the following shortcomings in practical applications: (1) This system adopts As a homogeneous catalyst for activating sodium persulfate to generate free radicals, the homogeneous catalyst is difficult to separate and recover from the reaction system, resulting in high reagent consumption and high operating costs; (2) It is easily oxidized during the reaction process. ,and Low conversion efficiency leads to decreased catalyst activity and waste of oxidant. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a GAC / NiO composite catalyst, its preparation method, and its application. The aim is to activate persulfate through heterogeneous catalysis to generate free radicals, thereby achieving effective separation and reuse of the catalyst and reducing reagent consumption and operating costs. Simultaneously, the stripped GAC / NiO composite catalyst can be separated from the cathode material through simple sieving. Furthermore, GAC itself can be used as a carbon source and reducing agent in subsequent pyrometallurgical recycling processes, further reducing energy consumption and costs associated with waste battery recycling.

[0006] To achieve the above objectives, the technical solution provided by the present invention is as follows:

[0007] A GAC / NiO composite catalyst is obtained by supporting NiO on the surface of activated carbon, i.e., impregnating activated carbon in an aqueous solution of nickel nitrate and then calcining it at high temperature.

[0008] The preparation method of the GAC / NiO composite catalyst as described above includes the following steps:

[0009] (1) Impregnation: Prepare 0.15-0.4 mol / L nickel nitrate ( The pretreated activated carbon (GAC) is immersed in a nickel nitrate aqueous solution for impregnation. The impregnated material is fully adsorbed and diffused into the pore structure of GAC, then filtered and the filter residue is dried.

[0010] (2) High-temperature calcination: The dried product is placed in a tube furnace and calcined at high temperature under a protective atmosphere. Under high temperature conditions, nickel nitrate decomposes into nickel oxide (NiO), and NiO particles are uniformly loaded on the surface and pores of GAC to obtain an activated carbon / nickel oxide composite catalyst, i.e., a GAC / NiO composite catalyst. At this calcination temperature, the main loaded material on the surface of activated carbon is NiO, which is the main active phase of the catalytic reaction.

[0011] Preferably, step (1) involves preparing 0.4 mol / L nickel nitrate ( Aqueous solution; the pretreated activated carbon in step (1) is commercially available granular activated carbon that has been repeatedly washed with deionized water to remove surface impurities and dust, and then dried to constant weight at 100-120℃.

[0012] Preferably, step (1) is performed according to the ratio of 1 mL of nickel nitrate ( Add 0.1g of pretreated activated carbon (GAC) to the aqueous solution; generally, the amount of activated carbon (GAC) added should be such that the solution remains green after immersion for 24 hours.

[0013] Preferably, the drying in step (1) is drying to constant weight at 80-120°C; the impregnation in step (1) is impregnation for 24 hours under constant temperature oscillation or magnetic stirring conditions.

[0014] Preferably, the protective atmosphere in step (2) is nitrogen or argon; in step (2), the heating rate is controlled at 4℃ / min to heat up to 600℃ for high-temperature calcination, and the holding time is 120min.

[0015] The application of GAC / NiO composite catalysts in the recycling of spent lithium-ion batteries, as described above.

[0016] As described above, the process involves adding dilute sulfuric acid to the positive electrode of a waste lithium battery, followed by sodium persulfate and the aforementioned GAC / NiO composite catalyst. After mixing and shaking, the mixture is ultrasonically treated to separate the aluminum foil and the positive electrode material from the waste lithium battery. The mixture is then filtered to obtain the final product.

[0017] Preferably, the added dilute sulfuric acid has a pH of 1.4.

[0018] Preferably, 50 mL of dilute sulfuric acid is added to every 1 square centimeter of waste lithium battery positive electrode; the amount of sodium persulfate used is 0.03 mol / L, that is, the amount of sodium persulfate added is such that its concentration in 50 mL of dilute sulfuric acid is 0.03 mol / L; the amount of GAC / NiO composite catalyst used is 1.2 g / L, that is, the amount of GAC / NiO composite catalyst is such that its concentration in 50 mL of dilute sulfuric acid is 1.2 g / L.

[0019] Preferably, the ultrasound is performed at an ultrasound temperature of 30°C, an ultrasound power of 100W, and an ultrasound reaction time of 20 minutes.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0021] The catalyst of this invention is used to remove GAC from the cathode material after stripping. In the pyrometallurgical recycling process, GAC can be used as a carbon source and a reducing agent to reduce metal oxides such as nickel, cobalt, and manganese, thereby reducing energy consumption and cost in the waste battery recycling process, achieving efficient and rapid stripping, and ensuring the integrity of the recycled aluminum foil. Furthermore, in the stripping method of this invention, most of the cathode material is stripped from the aluminum foil in sheet form, while GAC / NiO is in the form of fine particles. After the complete aluminum foil is sorted and recycled, the remaining cathode material and GAC / NiO mixture can be separated by sieving based on size differences, and GAC / NiO can be repeatedly recycled to achieve reuse. Attached Figure Description

[0022] Figure 1 The image on the left shows the positive electrode of a used lithium battery before it was stripped. Figure 1 The image on the right shows the aluminum foil obtained after peeling.

[0023] Figure 2These are SEM images of the GAC / NiO composite catalyst prepared in Example 1 at different magnifications.

[0024] Figure 3 This is the XRD pattern of the GAC / NiO composite catalyst prepared in Example 1.

[0025] Figure 4 These are XRD patterns of the cathode material before and after stripping in Example 3.

[0026] Figure 5 This is the XRD pattern of the aluminum foil after it was peeled off in Example 3. Detailed Implementation

[0027] The following is a detailed description of specific embodiments in conjunction with the accompanying drawings, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise specified, the raw materials and reagents used in the embodiments are commercially available. Waste lithium batteries are sourced from the commercially available ternary lithium batteries produced and used by Innovation Aviation Technology Group Co., Ltd.

[0028] Example 1

[0029] A method for preparing a GAC / NiO composite catalyst, comprising the following steps:

[0030] (1) Impregnation: Granular activated carbon (GAC) is repeatedly washed with deionized water to remove surface impurities and dust, and then dried at 100-110℃ to constant weight for later use; a 0.4 mol / L solution is prepared. Aqueous solution: Take 100 mL of the prepared nickel nitrate aqueous solution and add 10 g of the above-mentioned prepared GAC for immersion. The GAC was soaked in an aqueous solution for 24 hours under magnetic stirring. The resulting residue was filtered and dried at 80-90°C to constant weight.

[0031] (2) High-temperature calcination: The GAC dried to constant weight in step (1) was placed in a tube furnace and calcined at 600°C for 120 min under nitrogen atmosphere at a heating rate of 4°C / min to obtain the activated carbon / nickel oxide composite catalyst, i.e., the GAC / NiO composite catalyst. The obtained GAC / NiO composite catalyst was subjected to scanning electron microscopy and XRD scanning, and the results are as follows: Figure 2 , Figure 3 As shown. From Figure 2 , 3 As can be seen, SEM shows that NiO is uniformly dispersed in the form of nanoparticles, and XRD confirms that the phase of these particles is NiO. The combination of the two can more strongly prove that the present invention has successfully prepared a supported composite catalyst.

[0032] Example 2

[0033] A method for preparing a GAC / NiO composite catalyst, comprising the following steps:

[0034] (1) Impregnation: Granular activated carbon (GAC) is repeatedly washed with deionized water to remove surface impurities and dust, and then dried at 110-120℃ to constant weight for later use; a 0.15 mol / L solution is prepared. Aqueous solution: Take 100 mL of the prepared nickel nitrate aqueous solution and add 10 g of the above-mentioned prepared GAC for immersion. The solution is immersed in an aqueous solution in a constant temperature shaker for 24 hours (at room temperature). The solution is then filtered, and the filter residue is the GAC obtained after immersion. The GAC is then dried at 90-100℃ to constant weight.

[0035] (2) High-temperature calcination: The GAC dried to constant weight in step (1) is placed in a tube furnace and calcined at 600°C under argon atmosphere at a heating rate of 4°C / min for 120 min to obtain activated carbon / nickel oxide composite catalyst, i.e. GAC / NiO composite catalyst.

[0036] Example 3

[0037] Aluminum foil and cathode material stripped from the positive electrode of used lithium batteries

[0038] (1) Cut the positive electrode of the waste lithium battery into pieces of about 1cm × 1cm (e.g. Figure 1 (Left), with a mass of approximately 0.3g, the cut waste lithium battery positive electrode was placed in a beaker, and 50mL of dilute sulfuric acid solution with pH=1.4 was added. Then, approximately 0.3572g of sodium persulfate was added to make the concentration of sodium persulfate in 50mL of dilute sulfuric acid 0.03mol / L. Approximately 0.06g of the GAC / NiO composite catalyst prepared in Example 1 was added to make the concentration of GAC / NiO composite catalyst in 50mL of dilute sulfuric acid 1.2g / L. After mixing and shaking, the mixture was placed in an ultrasonic cleaner.

[0039] (2) Set the temperature to 30℃ and the ultrasonic power to 100W, start the ultrasonic cleaner, and react for 20 minutes to separate the aluminum foil and positive electrode material of the waste lithium battery positive electrode. After the reaction, filter to achieve solid-liquid separation, remove the aluminum foil, and rinse the surface with deionized water to obtain clean aluminum foil (e.g. Figure 1 (Right), complete the stripping and recycling. For example... Figure 4 As shown, the cathode material after stripping has the same characteristic peak as the electrode before stripping, which indicates that the crystal phase of the cathode material after stripping was not destroyed. Figure 5 As shown, the peeled aluminum foil has the same characteristic peaks as the standard aluminum card (PDF#04-0787), indicating that the crystal phase of the peeled aluminum foil is not damaged and can be reused.

[0040] The recycling of the composite catalyst in this invention: Most of the stripped cathode material is in sheet form. The dried cathode material is separated by passing it through a 70-mesh sieve. Large pieces of cathode material cannot pass through the sieve, while GAC / NiO, being fine particles, can, thus achieving separation of GAC / NiO and the cathode material. The separated and recovered GAC / NiO is dried and reused. Due to the presence of fine cathode material particles, the subsequent stripping efficiency of GAC / NiO is approximately 74% for the same mass.

[0041] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A GAC / NiO composite catalyst, characterized in that: The active phase NiO is supported on the surface of activated carbon, which is obtained by impregnating activated carbon with an aqueous solution of nickel nitrate and then calcining it at high temperature.

2. The preparation method of the GAC / NiO composite catalyst as described in claim 1, characterized in that, The operation includes the following steps: (1) Impregnation: Prepare a 0.15-0.4 mol / L nickel nitrate aqueous solution, immerse the pretreated activated carbon in the nickel nitrate aqueous solution, filter the impregnated material, and dry the filter residue; (2) High-temperature calcination: The dried product is calcined at high temperature under a protective atmosphere to obtain the GAC / NiO composite catalyst.

3. The preparation method of the GAC / NiO composite catalyst according to claim 1, characterized in that: Step (1) Prepare a 0.4 mol / L nickel nitrate aqueous solution; the pretreated activated carbon in step (1) is made by repeatedly washing granular activated carbon with water and then drying it to constant weight at 100-120℃.

4. The preparation method of the GAC / NiO composite catalyst according to claim 1, characterized in that: Step (1) Add 0.1g of pretreated activated carbon to every 1mL of nickel nitrate aqueous solution.

5. The preparation method of the GAC / NiO composite catalyst according to claim 1, characterized in that: The drying in step (1) is drying to constant weight at 80-120℃; the impregnation in step (1) is impregnation for 24 hours under constant temperature oscillator or magnetic stirring conditions.

6. The method for preparing the GAC / NiO composite catalyst according to claim 1, characterized in that: The protective atmosphere in step (2) is nitrogen or argon; in step (2), the heating rate is controlled at 4℃ / min to heat up to 600℃ for high-temperature calcination, and the holding time is 120min.

7. The application of the GAC / NiO composite catalyst as described in claim 1 or the GAC / NiO composite catalyst prepared by any of the methods in claims 2-6 in the recycling of waste lithium-ion batteries.

8. The application as described in claim 7, characterized in that: To separate the aluminum foil and cathode material of the waste lithium battery, dilute sulfuric acid is added to the positive electrode of the waste lithium battery, followed by sodium persulfate and the GAC / NiO composite catalyst. After mixing and shaking, the mixture is ultrasonically treated to separate the aluminum foil and cathode material of the waste lithium battery.

9. The application according to claim 8, characterized in that: The added dilute sulfuric acid has a pH of 1.4; the ultrasound is performed at an ultrasound temperature of 30°C, an ultrasound power of 100W, and an ultrasound reaction time of 20 minutes.

10. The application according to claim 8, characterized in that: The method involves adding 50 mL of dilute sulfuric acid to each 1 square centimeter of waste lithium battery positive electrode; the amount of sodium persulfate used is 0.03 mol / L; and the amount of GAC / NiO composite catalyst used is 1.2 g / L.